In vitro evaluation of different fungicides against Rhizoctonia solani and Alternaria citri infecting citrus - Sigdel, Susmita; Ranabhat, Saurav; Bhandari, Srijana; Magar, Prem Bahadur; Shrestha, Jiban; Subedi, Subash (Journal of Agriculture and Natural Resources, 2022)
Rhizoctonia solani and Alternaria citri are major plant pathogens of citrus, causing considerable production losses. Chemical fungicides are widely used for disease control. Using the food poisoning technique under in vitro conditions, an experiment was undertaken to investigate the efficacy of several fungicides against those pathogens. To evaluate the effect on Rhizoctonia solani mycelial growth, five different chemicals, viz. SAAF (Carbendazim 12% WP + Mancozeb 63% WP), Bavistin (Carbendazim 50% WP), VACOMIL PLUS (Metalaxyl 15% WP + Copper oxychloride 35% WP), and Raze (Copper oxychloride 50% WP) were used at 100 ppm and 200 ppm concentration each. Similar chemicals were used for Alternaria citri except for additional Mancozab (Mancozeb 75% WP). Mycelial growth inhibition was measured until the fungus nearly covered the plate in control. All fungicides reduced the fungal growth compared to control. After 96 hours of incubation with Rhizoctonia solani, maximum inhibition (100%) was achieved at both concentrations of Bavistin, followed by SAAF @ 200 ppm (97.59%) and SAAF @ 100 ppm (88.25%), whereas VACOMIL PLUS and Raze had the minimum effect on the mycelial growth. Similarly, after 8 days of incubation of Alternaria citri, SAAF @ 200 ppm showed the highest inhibition (70.86%), followed by SAAF @ 100 ppm (65.11%), Mancozab @ 200 ppm (64.39%), and Mancozab @ 100 ppm (47.48%), but the effect of Bavistin, Raze, and VACOMIL PLUS had the lowest impact. The chemical proven effective against the pathogens should be trialed in pot and field experiments for further verification.